Risk Management of the Maternal Care Telehealth Platform: A Case Study of Hallo Mama Using the ISO 31000:2018 Approach - Sherina Anggraini Mudjiono; Rhian Indradewa; Dimas Angga Negoro; Rian Adi Pamungkas (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
Maternal care telehealth platforms face multidimensional risks, including operational, data security, regulatory, and human resource challenges. This study analyzes risk management for Hallo Mama, a doula-based telehealth platform, using ISO 31000:2018 through a descriptive case study and RPN method. A total of 21 risks across six domains were identified, with six classified as high priority (RPN ? 15), including service delays, SOP violations, data breaches, staff burnout, privacy issues, and cash flow instability. After implementing targeted mitigation strategies, all residual risks decreased to medium levels (RPN 8–9). This study offers a practical risk management framework for digital maternal health startups in Indonesia